2009
DOI: 10.1016/j.nima.2008.11.113
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of thin MgAl films during hydrogen desorption

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. We used neutron reflectometry (NR) to study the structural changes of thin Pd-capped Mg 0.7 Al 0.3 and Mg 0.6 Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The exact reason why the hysteresis expands when the Mg/Pd interface is present remains unclear. Baldi et al [46] have proposed an explanation based on the elastic clamping of Mg layer by means of Pd, having affinity to form an alloy with Mg. This model suffers from explaining the complete (de-)hydrogenation behavior of Mg films, still, we think that the formation of Mg-Pd alloy at the interface is the main reason for the destabilization, observed in Pd capped Mg films.…”
Section: Hydrogenography Experiments On Mg/pd Filmsmentioning
confidence: 99%
“…The exact reason why the hysteresis expands when the Mg/Pd interface is present remains unclear. Baldi et al [46] have proposed an explanation based on the elastic clamping of Mg layer by means of Pd, having affinity to form an alloy with Mg. This model suffers from explaining the complete (de-)hydrogenation behavior of Mg films, still, we think that the formation of Mg-Pd alloy at the interface is the main reason for the destabilization, observed in Pd capped Mg films.…”
Section: Hydrogenography Experiments On Mg/pd Filmsmentioning
confidence: 99%
“…Mg-Al-Ti, Mg-Fe-Ti and Mg-Fe-Al. Because of encouraging results on Mg 70 Al 30 films [23][24][25], this Mg content was chosen as the starting point for the ternary alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Munter et al showed how deuterium absorption could be monitored in-situ during loading experiments on thin Pd films 9,10 . More recently, a series of studies has been published by Fritzche et al, showing how NR can be used to investigate the thermodynamics of hydrogen uptake process in Pd-capped metal alloy films [11][12][13][14][15] . NR has also proved an efficient way to characterize deviations in the hydrogen stoichiometry in very thin interface layers 9,16 , and can be used to determine inter-diffusion of elements at the interfaces of metal hydride films 11,12 .…”
mentioning
confidence: 99%